Menggugat Grand Strategi POLRI Yang Tak Kunjung Terwujud - Hasibuan, Edi Saputra (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2024)
This paper discusses the strategic plan of the Indonesian National Police. The purpose of this study is to evaluate the implementation of the National Police grand strategy towards 2025, especially Phase I or known as trust building in the implementation period of 2005-2010 and the second phase of Partnership Building for 5 years 2010-2015, This is done because towards Strive for Excellence in 2016-2025 in building the ability of public trust and public trust to go to the current stage of excellence is difficult to realize because trust building cannot be stable because it depends on legal events involving cases of police members and services of police members in the community.